Strategic planning: a human resource tool for higher education - Alvino, Kathleen M. (Washington, DC.: College and university personnel association, 1995)
Los temas principales de este libro son: What is strategic planning, what is the problem you are trying to solve, begin at the beginning, rightsizing, faculty and staff benefits: meeting the challenge of difficult financial times.
Keywords: Administración de Instituciones Educativas